The effects of Core Stability Exercises and Mulligan’s mobilization with movement techniques on sacroiliac joint dysfunction - Yan, Huiqian; Zhao, Peng; Guo, Xuanhui; Zhou, Xiao (Frontiers in Physiology, 2024)
Purpose：Sacroiliac joint dysfunction (SIJD), while being the primary contributor to low back pain, is still disregarded and treated as low back pain. Mulligan's Mobilization with Movement (MWM) Techniques and Core Stability Exercises (CSE) are often used to treat low back pain. There is not much evidence that it is effective in SIJD. To evaluate the effectiveness of CSE coupled with MWM (CSE+MWM) in the treatment of SIJD. Methods：39 patients with SIJD were recruited and randomly divided into distinct groups as follows: control group (n=13), CSE group (n=13) and CSE＋MWM group (n=13). The Numerical Pain Rating Scale (NPRS), the Roland Morris Disability Questionnaire (RMDQ), the Range of Motion (ROM), the Pressure Pain Threshold (PPT) and the pelvic tilt angle asymmetry ratio in the sagittal plane (PTAR) were used to gauge the intervention's success both before (M0) and after (M1) it. All experimental data were statistically analyzed. Results：The SIJ-related pain metric significantly decreased in both the CSE+MWM group and the CSE group between M0 and M1, as determined by the NPRS and RMDQ. Between M0 and M1, The CSE group's left axial rotation ROM and lumbar flexion ROM were significantly decreased. The CSE+MWM group's extension ROM and left lateral flexion ROM both significantly increased between M0 and M1. In the difference variable (M1-M0), the CSE+MWM group substantially outperformed control group in the left lateral flexion ROM and outperformed the CSE group in the left axial rotation ROM.Conclusion：In individuals with SIJD, CSE+MWM is beneficial in lowering pain, disability, and function. Treatment with CSE and MWM approaches for SIJ appears to boost this efficacy.